Computational studies on thermostability of endoglucanase from fusarium oxysporum - Waesoho, Shukree (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
Cellulose is the main component in plant cell and thus the most abundant biopolymer on earth. Cellulase is a group of enzymes that degrade cellulosic materials and belong to the O-glycoside hydrolases (EC 3.2.1.x). Endoglucanase (EC 3.2.1.4) is a key component in cellulase which has been used in various industries such as textiles, detergents, foods and animal feed, pulps and papers and recently in bio-fuel industries. Since most of the processes in many industries are carried out at higher temperature (above 60°C), the main limitation of cellulase utilization is the lack of enzyme activity and stability at higher temperatures. Generally, endoglucanases in glycoside hydrolase family 7 (GH 7) have the optimum temperature at 45-55°C and endoglucanase from Fusarium oxysporum (EGFO) completely loses activity after heating the enzymes at 60°C for three hours. In order to design a new thermostable endoglucanase from Fusarium oxysporum, molecular dynamics (MD) simulation technique was used to find out the dynamics factors responsible for the thermal stability of known endoglucanases (EG). Mesophilic endoglucanases from Fusarium oxysporum (EGFO) and thermophilic endoglucanase from Humicola insolens (EGHI) with known crystal structures and enzyme activitywere used to compare their dynamical behaviors at 40°C and 60°C using MD simulation in aqueous media. It has been found that the Root Mean Square Deviation (RMSD) backbone of EGFO tends to increase more rapidly at higher temperatures, whereas the RMSD values for EGHI either remains similar or decreases at higher temperature. The RMSD helices of EGFO also have the behavior similar to that RMSD backbone. The secondary structure conformation at the residues position 225 to 231 of EGFO changes significantly at higher temperature, whereas conformation of EGFO at these positions is maintained as the temperature is increased. The EGHI shows salt-bridge interactions and hydrophobic interactions in these regions. Hence these two factors are crucial for the thermal stability of endoglucanase, this information obtained was used to carry out several in silico mutations on EGFO with the objective of designing more thermostable endoglucanase and found that the dynamic behavior of newly designed mutants are consistent with the conclusions. Therefore, the new quintuple mutant obtained by mutating at the positions T224E/G229A/S230F/S231E/N321R is predicted to be more thermostable than EGFO.